2020
DOI: 10.1038/s41375-020-0934-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the SRC-family tyrosine kinase HCK as a therapeutic target in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive non-Hodgkin lymphoma subtype arising from naïve B cells. Although novel therapeutics have improved patient prognosis, drug resistance remains a key problem. Here, we show that the SRC-family tyrosine kinase hematopoietic cell kinase (HCK), which is primarily expressed in the hematopoietic lineage but not in mature B cells, is aberrantly expressed in MCL, and that high expression of HCK is associated with inferior prognosis of MCL patients. HCK expression is controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Previous studies have shown that HCK exerts a carcinogenic effect by regulating the ERK gene in BCR/ABL-positive ALL and B-ALL [13,15]. ERK1/2 pathway have been identi ed in human myeloid leukaemia, and abnormal activation enhances the proliferation and survival of myeloid cells [43]. In our study, we considered that HCK might regulate CDK6 expression through the ERK1/2-c-Myc axis.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that HCK exerts a carcinogenic effect by regulating the ERK gene in BCR/ABL-positive ALL and B-ALL [13,15]. ERK1/2 pathway have been identi ed in human myeloid leukaemia, and abnormal activation enhances the proliferation and survival of myeloid cells [43]. In our study, we considered that HCK might regulate CDK6 expression through the ERK1/2-c-Myc axis.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, SFK members exhibit complementary and often functionally redundant roles in several signal transduction pathways. For example, FYN and LCK cooperate in T-cell receptor-mediated activation, and HCK and FGR cooperate to regulate macrophage phagocytosis [13,34,46]. This functional overlap between SFK members has been shown to play an essential role in maintaining relatively normal immune responses, which may be the cause that the effect of HCK on the self-renewal ability of LSCs is not fatal.…”
Section: Discussionmentioning
confidence: 99%
“…The mutated form of MYD88 has been shown to trigger transcription and activation of HCK in Waldenström macroglobulinemia 57 , a disease that shares genetic and biological features with ABC DLBCL. HCK has been discussed as a possible therapeutic target for small molecule inhibitors in multiple cancers 58 and high expression of HCK has been associated with poor prognosis in mantle cell lymphoma 59 . Overexpression of HCK in other cancers can contribute to epithelial mesenchymal transition (EMT), hypoxia and TGFβ signaling 60 .…”
Section: Discussionmentioning
confidence: 99%